CD33+CD14+CD11b+HLA‐DR− monocytic myeloid‐derived suppressor cells recruited and activated by CCR9/CCL25 are crucial for the pathogenic progression of endometriosis. (16th November 2018) - Sun, Ya; Shao, Jun; Jiang, Feizhou; Wang, Yanqiu; Yan, Qin; Yu, Na; Zhang, Jin; Zhang, Jie; Li, Mingqing; He, Yinyan
Abstract : Problem: Endometriosis (EM) is a chronic immunoinflammatory disease associated with an abnormal immunotolerant microenvironment. Myeloid‐derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that play a major role in immunosuppression in cancer, inflammation and other diseases. This paper aims to elucidate whether or not MDSCs are involved in regulating this microenvironment in EM and how this regulation occurs. Method of Study: Immunochemistry (IHC) and qPCR were conducted to measure CD11b and ARG1 expression in the ectopic endometrium samples from EM patients. CCL25 levels in EM PF and the expression of CCR9 on M‐MDSCs were measured by ELISA. M‐MDSC migration was determined towards rhCCL25, α‐CCR9, α‐CCL25 and EM PF through in vitro chemotaxis assay. CD33 + CD14 + CD11b + HLA‐DR ‐ M‐MDSCs isolated from EM PBMCs were added to CD8 + T cells stimulated with α‐CD3/α‐CD28 antibody. After 72 hours of co‐culture, proliferation was measured to rate the immunosuppressive function of M‐MDSCs. Finally, levels of IL‐10, GM‐CSF and arginase activity in the cultured supernatants were detected. Results: IHC and qPCR results revealed higher CD11b and ARG1 expression in EM endometrium than normal endometrium. MDSCs accumulated in the EM microenvironment, in which M‐MDSCs were the predominant type. CD33 + CD14 + CD11b + HLA‐DR − M‐MDSCs expressed high CCR9 levels and were recruited through CCL25. M‐MDSCs from EM PBMCs inhibited proliferation and activity in autologous T cells. rhCCL25 promoted IL‐10 and GM‐CSF secretion and arginase enzymatic activity in CD33 + CD14 + CD11b + HLA‐DR − M‐MDSCs. Conclusion: CD33 + CD14 + CD11b + HLA‐DR − M‐MDSCs recruited and activated by CCR9/CCL25 play a crucial role in the pathogenic progression of endometriosis, thus providing a potential target for EM treatment.